Antígenos da forma amastigota de Leishmania chagasi identificados por dupla varredura da biblioteca de cDNA - Salha, Daniella Regina Arantes Martins (2006)
Control of human visceral leishmaniasis in endemic regions is hampered in part by the lack of knowledge with respect of the role reservoirs and vector. In addition, there is not yet an understanding of how non-symptomatic subclinical infection might influence the maintenance of infection in a particular locality. Of worrisome is the limited accessibility to medical care in places with emerging drug resistance. There is still no available protective vaccine either for humans or other reservoirs. Leishmania species are protozoa that express multiple antigens which are recognized by the vertebrate immune system. Since there is not one immunodominant epitope recognized by most hosts, strategies must be developed to optimize selection of antigens for prevention and immunodiagnosis. For this reason, we generated a cDNA library from the intracellular amastigote form of Leishmania chagasi, the causative agent of South American visceral leishmaniasis. We employed a two-step expression screen of the library to systematically identify T and T-dependent B cell antigens. The first step was aimed at identifying the largest possible number of clones producing an epitope-containing polypeptide with a pool of sera from Brazilians with documented visceral leishmaniasis. After removal of clones encoding heat shock proteins, positive clones underwent a second step screen for their ability to cause proliferation and IFN-γ responses of T cells from immune mice. Six unique clones were selected from the second screen for further analysis. The clones encoded part of the coding sequence of glutamine synthetase, transitional endoplasmic reticulum ATPase, elongation factor 1γ, kinesin K-39, repetitive protein A2, and a hypothetical conserved protein. Humans naturally infected with L. chagasi mounted both cellular and antibody responses to these protein Preparations containing multiple antigens may be optimal for immunodiagnosis and protective vaccines against Leishmania